PRESENTATION DIFFICULTIES EXPERIENCED BY STUDENTS OF ENGLISH DEPARTMENT OF UNSWAGATI - Widyastuti, Tiara; Mahaputri, Ratna Andhika (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2015)
This research is aimed to know how the students make the presentation in the classroom. This research wants to explore the studentsâ difficulties in presenting the material. The research was conducted at Unswagati Cirebon toward fifth semester of A and B class. This research uses descriptive qualitative approach and use observation, and questionnaire as instruments in collecting data. Then the result of this research is presented descriptively. The findings of this research show that most of the students give good criteria in make presentation in the classroom, they can deliver the presentation well. The difficulties that faced by the student when presenting the material consist of: the students bring note when they presenting the material, they often fidgeting, jiggling or swaying when they deliver the presentation, the student stiff when deliver the presentation and it makes presentation tedious, and they end the presentation with an inspiration deficit. Keywords: Student, Difficulties, Presentation.